Interlaboratory comparison of the TransFix®/EDTA Vacuum Blood Collection tube with the 5 mL Cyto‐Chex® BCT. Issue 6 (24th October 2018) - Harrison, Daniel; Ward, Rosalie; Bastow, Sarah; Parr, Andrew; Macro, Susan; Wallace, Paul K.
Abstract : Background: An interlaboratory study was performed to compare the performance of the 3 mL TransFix®/EDTA Vacuum Blood Collection Tube (TVT), with the 5 mL Cyto‐Chex® BCT tube (BCT). Both devices are intended for collection and storage of whole blood specimens for immunophenotyping of leukocytes by flow cytometry for up to 14 days. Methods: One site in the United States and two in the United Kingdom tested samples from 10 HIV positive patients and four healthy subjects for a total of 42 samples. From each subject, three blood samples were collected: a BD 4 mL K3 EDTA Vacutainer (Vacutainer), a TVT, and a BCT. At all sites, samples were analyzed on a BD FACS Canto II flow cytometer for a full lymphocyte subset count within 6 h of collection (all devices) and on Day 11 and Day 15 (TVT and BCT only). Data obtained from the Vacutainer were used as the control data set with which TVT and BCT data were statistically compared. Results and Conclusions: Statistical concordance was demonstrated for both devices in relation to cell absolute count recovery. For cell marker signal, both devices exhibited a significant decrease in mean fluorescence intensity (MFI) for the detection of lymphocyte subsets and their target markers. There was a marked increase in autofluorescence observed for BCT stabilized lymphocytes whereas values for the TVTs were comparable to the control. There were eight instances of statistical equivalence between the level of antibody autofluorescence observed in the control tube and the TVT across both patient cohorts, versus two for the BCT. © 2018 International Clinical Cytometry Society